FOREST DEVELOPMENT IN TAHURA POCUT MEURAH INTANAREA AND ITS COUNTERMEASURES: PENGEMBANGAN HUTAN DI KAWASAN TAHURA POCUT MEURAH INTAN DAN PENANGGULANGANNYA - Desyan Ria; Aidil Amar; Nuraida; Rayhatul Jannah (PT. ROCE WISDOM ACEH, 2025)
Forest development remains a significant challenge in Indonesia, including in the Pocut Meurah IntanForest Park (Tahura), Aceh. This Tahura is one of the conservation areas that has high biodiversityand essential functions for surrounding communities and regional ecosystems. Tahura Pocut MeurahIntan is located in Aceh Besar District and Pidie District, with an area of approximately 6,300hectares. The results showed that forest destruction in TAHURA Pocut Meurah Intan was caused byseveral primary factors, namely: Illegal logging: Illegal logging activities for commercial purposes arethe leading cause of damage to forest ecosystems. Land encroachment: Changes in forest function toagricultural or residential land are carried out by the surrounding community due to limited productiveland. Illegal mining activities: Unregulated mining in the TAHURA area causes damage to the soilstructure and contributes to forest degradation. Impacts include ecosystem degradation, biodiversityloss, and social conflict. Countermeasures require community-based management, strengthenedregulations, and economic diversification through ecotourism. The involvement of local communitiesand modern technology can support both conservation and sustainable welfare